Rice Husk Ash Incorporation in Container Substrates Effect on Romaine Lettuce Plant Growth - Sreyhor Mot; Sophary Khin; Vibol Peuo; Panha Pok; Pao Srean (AGRITROPICA : Journal of Agricultural Sciences, 2021)
Primary substrate components include peat moss, vermiculite, perlite, bark, and compost are commonly-used substrate in horticultural crop production.These substrate components are high cost due to the extreme cost of transportation, fuel for extraction, and processing. Local rice husk ash (RHA) as an alternative substrate component was used to evaluatethe growth of Romaine Lettuce plants in response to the application of different incorporations of RHA in container substrates. The test was conducted with a completely randomized design of four RHA treatment, rates at 0%, 10%, 30%, and 50% (by vol.), with 10 replicates. The results showed that plant stem elongation increased with decreased incorporations of RHA application. Although the fresh weight of plants(shoot or root)and number of leaves increased with the RHA application, no significant difference for the plant biomass produced (dry weight of root and shoot) betweenthe 30% and 50% RHA treatments. The RHA can be used as a local and low cost substrate component; and the incorporation of 30% (by vol.) RHA in container substrates is a certain amount for lettuce plant growth.